2020
DOI: 10.1038/s41467-020-19382-9
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception alters vaginal microbiota and cytokines in South African adolescents in a randomized trial

Abstract: Young women in sub-Saharan Africa are disproportionally affected by HIV infection and unintended pregnancies. However, hormonal contraceptive (HC) use may influence HIV risk through changes in genital tract microbiota and inflammatory cytokines. To investigate this, 130 HIV negative adolescent females aged 15–19 years were enrolled into a substudy of UChoose, an open-label randomized crossover study (NCT02404038), comparing acceptability and contraceptive product preference as a proxy for HIV prevention delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 64 publications
7
81
0
1
Order By: Relevance
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase. [33][34][35] Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL-6 and IL-1β during CVR use (in addition to IFNγ and TNFα, which we did not find). The third study used cervicovaginal lavage samples and a cross-sectional design 35 and the results agreed less well with ours, in particular, their finding that IL-1β was lower in CVR users.…”
Section: Cvr Use Compared To Menstrual Cycle Phasessupporting
confidence: 85%
See 1 more Smart Citation
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase. [33][34][35] Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL-6 and IL-1β during CVR use (in addition to IFNγ and TNFα, which we did not find). The third study used cervicovaginal lavage samples and a cross-sectional design 35 and the results agreed less well with ours, in particular, their finding that IL-1β was lower in CVR users.…”
Section: Cvr Use Compared To Menstrual Cycle Phasessupporting
confidence: 85%
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase 33‐35 . Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL‐6 and IL‐1β during CVR use (in addition to IFN‐γ and TNF‐α, which we did not find).…”
Section: Discussionsupporting
confidence: 70%
“…Ten studies investigated the effect of the combined oestrogencontaining OCP on the vaginal microbiome (Borgdorff et al, 2015;Borgdorff et al, 2017;Brooks et al, 2017;Onywera et al, 2019;Wessels et al, 2019;Balle et al, 2020;Song et al, 2020;van de Wijgert et al, 2020;Ratten et al, 2021); six reported a positive effect on the vaginal microbiota, and four reported neutral findings (Tables 1 and 3).…”
Section: Oestrogen-containing Oral Contraceptive Pillsmentioning
confidence: 99%
“…Three studies investigated the effect of the oestrogen-containing CVR (Borgdorff et al, 2017;Crucitti et al, 2018;Balle et al, 2020). Compared to baseline specimens, Borgdorff et al (2017) found that CVR-use was associated with a non-significant decrease in the relative abundance of G. vaginalis and Crucitti et al ( 2018) found CVR-use was associated with a significant decrease in the prevalence G.vaginalis and A.vaginae (Table 1).…”
Section: Oestrogen-containing Contraceptive Vaginal Ringmentioning
confidence: 99%
“…Eighteen studies used agematched women not using hormonal contraceptives as the comparator group (e.g. no contraceptives or condom-use) (low risk), and seven used the baseline specimen prior to contraception initiation as the comparator group (low/medium risk) (Jacobson et al, 2014;Bassis et al, 2015;Achilles et al, 2018;Crucitti et al, 2018;Tuddenham et al, 2019b;Yang et al, 2019;Balle et al, 2020). Five studies did not stratify hormonal contraceptive exposure by oestrogen-containing or progestinonly (high risk) (Gautam et al, 2015;Scott et al, 2019;Tuddenham et al, 2019a;Tuddenham et al, 2019b;Marconi et al, 2020).…”
Section: Studies Reporting On the Effect Of Hormonal Contraceptives On The Vaginal Microbiota Among Reproductive-aged Womenmentioning
confidence: 99%